Lithostratigraphy of Sicily - Basilone, Luca (UNIPA Springer Series,, 2018)
This book offers as comprehensive an overview as possible of the lithostratigraphy of the Italian region of Sicily, taking into account the multiplicity of formational and terminological variability developed over more than a century of studies and publications. It presents stratigraphic terminology, the geological lexicon and the main stratigraphic subdivisions that are not familiar to Sicilian geologists. The new stratigraphic methods and the use of formations as mapping units have prompted the acquisition of new lithostratigraphic data, and a review of the previous units and their comparison with the new collected data, enabling the definition of a number of new lithostratigraphic units. The book summarizes the results in 77 worksheets containing the most important information regarding the lithological, sedimentological and microfacies characteristics, the measured thicknesses, areal extent and the regional aspects, the paleoenvironmental, paleogeographic and paleo-tectonics setting, compiled according to standard procedures and nomenclature rules provided by the International Commission on Stratigraphy (ICS).